Seasonal and Long-Term Features of the Distribution of the Vegetation Index NDVI on Arable Lands in Bryansk Region - LOBANOV, Gregory V.; TRISHKIN, Boris V.; AVRAMENKO, Marina V.; CHAROCHKINA, Anna Yu.; PROTASOVA, Alina P. (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018, 2018)
The features of the multi-year distribution of vegetation indices are considered as an indicator of the favorable conditions for farming, the correspondence of the set of crops with the soil, geomorphological, microclimatic characteristics of the agrolandscape. The authors presented methodical problems of using information about NDVI for remote determination and monitoring of soil properties through bioproductivity. Methods of collecting and systematizing information on the seasonal and long-term dynamics of NDVI (according to MODIS data) and some factors of the spatial distribution of its mean values were used for a detailed study of the issue. The possible mechanisms of influence of the surface slope (the values are determined by SRTM), the average humus content, the mechanical strength of soils on the NDVI distribution were shown. Information on NDVI arable land changes in the Bryansk region in the years with different meteorological conditions (2010-2015) was given. The general features of NDVI seasonal dynamics within the vegetation period were described – from late March to early November. The influence of meteorological factors on the distribution of NDVI was determined. Synchronous differences in the dynamics of NDVI for groups of arable land plots homogeneous in the state of the surface slope and agrotechnical characteristics of soils were justified from the position of seasonal dynamics of landscapes. A complex ratio of the significance of groups of factors was shown, possible models for explaining their differences in space and time were proposed.